Orbital Tumors Diagnosis and Treatment - Karcioglu, Zeynel A.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
Lavishly illustrated and clinically relevant, Orbital Tumors: Diagnosis and treatment presents a single-volume reference for orbital pathology in daily practice. Chapters written by leading practitioners in ophthalmology, obitology, radiology, pathology, neurosurgery, medical and radation oncology, and plastic surgery provide a range and depth of expertise unavailable elsewhere. In order to provide the most recent developments in the science of orbitology, Orbital Tumors explores the latest developments in medical genetics, molecular genetics, and immunosurveillance mechanisms of neoplasia. The occurrence of multiple, malignant neoplasms in retinoblastoma have been included to apply molecular concepts to clinical practice related to orbital tumors. In the realm of clinical practice for orbital pathology, no development has been more influential than the revolution in imaging techniques, including ultrasonography, computerized tomography, and magnetic resonance methods. The implications of these improvements in diagnostic capabilities are fully explored and explained in Orbital Tumors. The text also includes diagnostic advances in immunohistochemistry, flow cytometry, gene microarray, and the polymerase chain reaction. These are summarized in a separate chapter on orbital biopsy. Orbital Tumors also includes current staging of malignant orbital tumors, advances and techniques in surgical treatments, radiation advances and options, and the most recent chemotherapeutic therapies for both pediatric and adult tumors. Orbital Tumors will become and indispensible tool not only for general ophthalmologists, but also for oculoplastic surgeons and orbitologists in their daily practice. The book has further reach as a reference for pediatricians, radiologists, pathologists, neurosurgeons, and otolaryngologists who deal with orbital tumors.
Current Concepts of Oncogenesis -- Molecular Models of Cancer Development -- Immune Surveillance and Cancer Pathogenesis -- The Changing Nature and Behavior of Orbital and Periorbital Tumors -- Mechanisms of Tumor Metastasis in the Orbit -- Multiple Malignancies in Retinoblastoma -- Diagnosis of Orbital Tumors -- Clinical Evaluation of the Orbit -- Neuro-Ophthalmologic Evaluation of the Orbit -- Ultrasonography in Orbital Differential Diagnosis -- The Basics of Orbital Imaging -- Imaging in Orbital Differential Diagnosis -- New Concepts in Orbital Imaging -- Orbital Biopsy -- Primary Tumors of the Orbit -- Orbital Lymphoma -- Vascular Tumors -- Fibrohistiocytic Tumors -- Fibro-osseous and Cartilaginous Tumors and Tumorlike Conditions -- Peripheral Nerve Tumors -- Lacrimal Gland Tumors -- Tumors of the Lacrimal Drainage System -- Secondary Tumors of the Adult Orbit -- Eyelid and Periocular Skin Tumors -- Conjunctival Tumors -- Ocular Tumors -- Tumors of the Cranial and Nasal Cavities and Paranasal Sinuses -- Metastatic Tumors -- Pediatric Orbital Tumors and Pseudotumors -- Benign Pediatric Tumors -- Malignant Pediatric Tumors -- Tumorlike Conditions in the Orbit -- Orbital Inflammation and Infection Versus Neoplasia -- Graves Disease -- Mass-Forming Inflammatory Lesions of the Orbit -- Management of Orbital Tumors -- Staging of Orbital Tumors -- Surgical Treatment -- Computer Image Guidance and Skull-Base Strategies -- Radiation Treatment -- Chemotherapy for Childhood Tumors -- Chemotherapy for Adult Tumors.
Keywords: Medicine; Oncology; Ophthalmology; Pathology; Medicine & Public Health; Ophthalmology; Pathology; Oncology; Electronic books